Research status and prospects of treatment for malignant pleural mesothelioma - ZHAO Kaile, WANG Lei, GENG Jianxiong, CUI Chengwei, YU Yan (Zhongguo aizheng zazhi)
Malignant pleural mesothelioma (MPM) is strongly associated with a history of asbestos exposure and is characterized by high malignancy, high mortality, and poor prognosis. Current treatments for MPM are limited and generally suboptimal, resulting in a median overall survival (OS) of approximately one year for MPM patients. However, advancements in treatment options, including surgery, radiotherapy, chemotherapy, immunotherapy and targeted therapy, have brought new hope to patients with MPM. For early-stage MPM patients categorized under the TNM staging system, surgical treatment is feasible and can improve survival rates and quality of life. However, there is still debate regarding the optimal surgical approach for MPM. In addition to surgery, radiotherapy plays a vital role in MPM treatment. It is often used as prophylactic treatment or for alleviating local symptoms in advanced stages. Radiotherapy can also serve as neoadjuvant or adjuvant therapy in surgical contexts. For patients experiencing local progression or isolated distant metastases after systemic treatment, radiotherapy is a viable option. The advent of advanced radiotherapy techniques, such as intensity-modulated radiotherapy (IMRT) and volumetric intensity-modulated arc therapy (VMAT), has significantly improved the precision and efficacy of radiotherapy while minimizing damage to healthy tissues. Furthermore, brachytherapy can relieve pain or act as a localized supplemental therapy. Chemotherapy remains the standard treatment for MPM. The combination of pemetrexed and platinum-based drugs is widely applied as first-line therapy and has been shown to significantly extend survival. However, commonly used second-line regimens often yield suboptimal results. In recent years, immunotherapy has developed rapidly. Dual immunotherapy with nivolumab and ipilimumab has demonstrated impressive clinical efficacy and safety. The combination of immunotherapy and chemotherapy has also notably extended patients' median survival. Multiple clinical trials have confirmed that this combination therapy benefits patients. Currently available targeted therapies for MPM primarily focus on anti-angiogenesis. Bevacizumab combined with chemotherapy has established its position as a first-line treatment. Research on ramucirumab and apatinib suggests that these drugs have certain efficacy and safety profiles. Beyond conventional treatment options, the UV1 cancer vaccine combined with dual immunotherapy offers new hope for patients. Chimeric antigen receptor T (CAR-T) cell therapy is an emerging treatment method being investigated in MPM patients, with phase Ⅰ clinical trials demonstrating good antitumor effects. Additionally, some antibody-drug conjugates are becoming therapeutic options for MPM through precise targeting. Tumor treating fields combined with chemotherapy has also shown efficacy in extending survival. Despite the increasing variety of treatment options for MPM, its diagnosis and treatment still face numerous challenges, including difficulties in early detection, treatment resistance, and a lack of large-scale evidence-based clinical studies. Future research should focus on improving early diagnosis rates, developing new treatment strategies, overcoming resistance, and advancing personalized therapy. Strengthening the integration of basic research and clinical trials will also be essential. Through multidisciplinary collaboration and continuous innovation, it is hoped that more effective and safer treatment options will become available, ultimately improving the prognosis of MPM patients.